The Resistance Movement of Aboriginal People To Fight Against The Plans For A Nuclear Waste Dump In South Australia - Korwa, Johni R.V. (Papua Law Journal, 2017)
Aborigine is the indigenous people of Australia who have attempted to oppose the proposal for South Australia to host an international nuclear dump. Even though the rights of indigenous people have been recognized by the United Nations Declaration on the Rights of Indigenous Peoples, the treatment they receive are not in accordance with the standard of living. The object of this this paper is to examine the struggle of Aboriginal Australia as indigenous people who seek to ensure their basic rights to clean environment from nuclear waste by using normative juridical method. The results of the paper show that Aboriginal people have commenced their struggle by the formation of global movement in the form of local campaign (Kupa Piti Kungka Juta), Australian Nuclear Free Alliance (ANFA), in collaboration with Amnesty International and the International Campaign to Abolish Nuclear Weapons (ICAN). All efforts are made to pressure the Australian government not to consider South Australia as a nuclear waste disposal site. This is because nuclear waste can have an impact on public health and environmental damage, trigger nuclear war, and become a threat to the land of Aboriginal people.